High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Investigation of future climate change over the British Isles using weather patterns - James O. Pope; Kate Brown; Fai Fung; Helen M. Hanlon; Robert Neal; Erika J. Palin; Anne Reid (Climate Dynamics, 2022)
For those involved in planning for regional and local scale changes in future climate, there is a requirement for climate information to be available in a context more usually associated with meteorological timescales. Here we combine a tool used in numerical weather prediction, the 30 weather patterns produced by the Met Office, which are already applied operationally to numerical weather prediction models, to assess changes in the UK Climate Projections (UKCP) Global ensemble. Through assessing projected changes in the frequency of the weather patterns at the end of the 21st Century, we determine that future changes in large-scale circulation tend towards an increase in winter of weather patterns associated with cyclonic and westerly wind conditions at the expense of more anticyclonic, settled/blocked weather patterns. In summer, the results indicate a shift towards an increase in dry settled weather types with a corresponding reduction in the wet and windy weather types. Climatologically this suggests a shift towards warmer, wetter winters and warmer, drier summers; which is consistent with the headline findings from the UK Climate Projections 2018. This paper represents the first evaluation of weather patterns analysis within UKCP Global. It provides a detailed assessment of the changes in these weather patterns through the 21st Century and how uncertainty in emissions, structural and perturbed parameters affects these results. We show that the use of these weather patterns in tandem with the UKCP projections is useful for future work investigating changes in a range of weather-related climate features such as extreme precipitation.